The Workplace Environment, Employees’ Retention, and Performance: A Focus on Non-Voiced BPO Employees for an Enhance Staff Development Program - Eunice Rain E. De Jesus; Hillard D. Noveno; Noemie E. Villamor; Jerico B. Tadeo; Xavier Lawrence D. Mendoza (Garuda Prestasi Nusantara Consulting, 2023)
The business process outsourcing (BPO) Industry is known for being one of the most stressful service industries in its workforce. The main objective of this study is to identify the different factors that affect the work environment, employees’ retention, and performance of non-voice BPO employees. The authors used descriptive-causal to identify the factors and socio-demographic profile of the respondents. The 250 respondents were purposively selected from five different BPO companies in the National Capital Region (NCR). Considerably, the results revealed that most of employees are female, are 18 to 24 years old, earn between Php16,000 and Php21,000 monthly, are single, and college undergraduates. The study found out that leadership performance management system, health and safety policies, personal development, and organizational culture are factors that affect the work environment, employees’ retention, and performance of non-voice BPO employees. Considerably, it was revealed that there was no significant relationship between socio-demographic profile of the respondents and the extent factors that affects the work environment, employees’ retention, and performance of non-voice BPO employees. The researchers recommend this study to intensify monetary and non-monetary benefits as well as creation of employee centered program within the workplace. Keywords: business process outsourcing, non-voice employee, workplace environment, employee retention, performance.